2013
DOI: 10.1007/s00381-013-2244-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of ventriculoperitoneal shunt valve design in the treatment of pediatric hydrocephalus—a single center study of valve performance in the clinical setting

Abstract: This study confirmed important risk factors for shunt failure in children. Despite certain limitations and biases, similar findings for both valves examined in the clinical setting were obtained. Thus, valve type does not seem to influence risk of shunt failure. Prospective, randomized, and controlled trials are required to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Premature infants had a higher risk of shunt failure. 10 Intraventricular hemorrhage (an underlying cause of hydrocephalus), a younger age, and a lower weight at the time of initial shunt placement were shown to be directly correlated with an increased risk of VP shunt failure. 3,10 On the other hand, the case series reported by Miranda et al 2 indicated that rates of shunt obstruction in preterm-related post-hemorrhagic hydrocephalus was high but did not seem to be higher than in other groups with pediatric hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Premature infants had a higher risk of shunt failure. 10 Intraventricular hemorrhage (an underlying cause of hydrocephalus), a younger age, and a lower weight at the time of initial shunt placement were shown to be directly correlated with an increased risk of VP shunt failure. 3,10 On the other hand, the case series reported by Miranda et al 2 indicated that rates of shunt obstruction in preterm-related post-hemorrhagic hydrocephalus was high but did not seem to be higher than in other groups with pediatric hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, failure of a fixed-pressure valve system requires valve replacement which is accompanied by the risk of complication. Limiting the need for repeat surgical intervention is a crucial advantage to programmable valves; however, they are accompanied by their own complications [6,10,11], and there is evidence to suggest that shunt survival is not significantly different from that of fixed-pressure valves [12,13]. Given their complex mechanisms, these valves are typically more expensive than their fixed-pressure counterparts, and the debate over the cost-benefit is ongoing [10].…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of shunt systems are currently available to clinicians, but their impact on shunt failures rates is unclear. Notarianni et al did not find a difference in the rates of shunt failure in comparing programmable systems with pressure-controlled or valveless shunts, and recent studies with newer valves have not found a difference in revision rates by valve type [2,12]. However, the rates of shunt failure remain high, and new methods are needed to ensure shunt survival [24].…”
Section: Shunt Outcomesmentioning
confidence: 92%